STUDI ANALISIS TENTANG TINGKAT KESEGARAN JASMANI SISWA KELAS X SMAN 1 KABAWO - Samsidar; Muhammad Rusli; Suhartiwi (Journal Olympic (Physical Education, Health and Sport), 2022)
The purpose of this study was to determine the level of physical fitness of female students of class X SMAN 1 Kabawo. The population in this study were all students of class X SMAN 1 Kabawo, totaling 253 people consisting of 120 boys and 133 girls. The sample in this study was obtained by purposive sampling technique, namely the sample was selected by considering the gender of the woman, so that the sampling was 30% of the total population and obtained a sample of 40 people. The instrument used in the study was the Indonesian physical fitness test (TKJI) for children aged 16-19 which consisted of: running 60 meters, hanging bent elbows, lying down for 60 seconds, jumping upright and running 1000 meters. The technique used to obtain research data is the percentage description statistics. The results showed that based on the analysis study of the physical fitness level of female students of class X SMAN 1 Kabawo as a whole, the data obtained were: there were 0 students with a percentage of 0% who had a very good physical fitness level, there were 3 students with a percentage of 8% who had a good physical fitness level, There are 24 students with a percentage of 60% having a moderate level of physical fitness, there are 13 students with a percentage of 33% having a low level of physical fitness, and there are 0 students with a percentage of 0% having a very low level of physical fitness. So it can be concluded that based on the analysis study of the physical fitness level of female students of class X SMAN 1 Kabawo is dominant or generally falls into the moderate category.